About Nasiruddin Tusi's Life, Work and Teachers (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
From time immemorial, knowledge and enlightenment are considered to be the qualities and virtues that glorify a person, and the role and work of the teachers who taught him the knowledge that taught him in the path of life of every thinking scientist is considered worthy of praise. Nasiruddin Tusi was born in Tus in 1201 in the family of Sheikh Vajhiddin ibn Hasan, known as Firuzshah Jehrudi. Tusi, who received his initial education from his father Muhammad ibn Hasan, surprised teachers and people of knowledge with his talent. Nasiriddin Tusi, distinguished by his unique ability, later studied with Farididdin Damadin. He learned the knowledge of Sharia from his father, and his initial education from the mathematician and logician Nasiruddin Muhammad Shai, and the sciences of fiqh, hadith and geometry from Nasriddin Abdullah bin Hamza. Nasriddin Abdallah ibn Hamza, who was busy teaching subtle and gentle aspects of Islam, named his favorite student "Nasiruddin" - the Arabic word means defender of religion, helper of religion.The article describes the results of research on Tusi's life, work, and the teachers he studied with.